2013
DOI: 10.5539/jps.v2n2p61
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Methanolic Extracts, Decoction and Isolated Triterpene Products from Different Parts of Birch, Betula pendula, Roth

Abstract: Five methanolic extracts obtained from different parts of birch, Betula pendula, Roth. (external and internal bark, flowers, leaves and buds), were evaluated for their antibacterial activity in this study. Triterpene compounds, betulin, betulinic acid, oleanolic acid and lupeol, were isolated from the external parts of birch bark using the method of dry column chromatography (DCC) as well as preparative thin layer chromatography (TLC). These compounds were also investigated for their antibacterial activity. Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 10 publications
2
29
0
Order By: Relevance
“…Antibacterial and antimicrobial activity of different birch parts in general should be further explored when used as herbs and in herbal preparations (Duric et al, 2013). We confirm low antibacterial effect of Betula pendula only against S. typhimurium (4.3 mm).…”
Section: Resultssupporting
confidence: 60%
“…Antibacterial and antimicrobial activity of different birch parts in general should be further explored when used as herbs and in herbal preparations (Duric et al, 2013). We confirm low antibacterial effect of Betula pendula only against S. typhimurium (4.3 mm).…”
Section: Resultssupporting
confidence: 60%
“…Results showed that BA was inactive against all strains tested, indicating that isolated betulinic acid is not involved with the antimicrobial activity presented by DCMF, although we cannot rule out a possible synergism between BA and other components. These results are in agreement with previous studies which also verified that BA was inactive against S. aureus and E. coli (Fontanay et al 2008;Silva et al 2012;Duric et al 2013). However, another study verified that BA was weakly active against E. coli (MIC 512 lg ml À1 ) and moderately active against S. aureus (MIC 256 lg ml À1 ), with its inhibitory effect caused by an enhanced electron transport chain activity leading to an increased oxidative stress in the bacterial cells (Oloyede et al 2017).…”
Section: Resultssupporting
confidence: 94%
“…; Duric et al . ). However, another study verified that BA was weakly active against E. coli (MIC 512 μ g ml −1 ) and moderately active against S. aureus (MIC 256 μ g ml −1 ), with its inhibitory effect caused by an enhanced electron transport chain activity leading to an increased oxidative stress in the bacterial cells (Oloyede et al .…”
Section: Resultsmentioning
confidence: 97%
“…Here, we report for the first time the prominent anti-QS properties of Betula verrucosa buds (non-pigmented zone area of 89-113 mm 2 ), while direct antibacterial properties of birch extracts were shown earlier (27). We are also reporting the anti-QS activity of Eucalyptus viminalis leaves (75-276 mm 2 ), which agree well with data on the anti-QS properties of Eucalyptus oil (28) as well as a significant reduction in QS-mediated biofilm formation by Eucalyptus globulus extracts (29).…”
Section: Regulatory Effects Of Plant Extracts On C Violaceum Pigmentmentioning
confidence: 99%